2014
DOI: 10.1002/asia.201402765
|View full text |Cite
|
Sign up to set email alerts
|

Reaction‐Based Fluorescent Probe for Detection of Endogenous Cyanide in Real Biological Samples

Abstract: Herein, two compounds (1 a and 1 b) were rationally constructed as novel reaction-based fluorescent probes for CN(-) by making use of the electron-withdrawing ability of the cyano group that was formed from the sensing reaction. Notably, this design strategy was first employed for the development of fluorescent CN(-) probes. The experimental details showed that probe 1 a exhibited a fluorescence turn-on response to CN(-), whereas other anions, biological thiols, and hydrogen sulfide gave almost no interference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Many metal complexes are known in the literature for the detection of cyanide using colorimetric and fluorescent approaches. However, most of these reported complexes needed expensive reactants, multistep synthesis of ligand, purification by different separation techniques, and different characterization techniques were required, and they are very time-consuming. To avoid the multistep synthesis and characterization, we have found that an off-the-shelf compound, 6,7-dihydroxycoumarin ( 1 ), is suitable to make a complex with copper in water and thereby binds with cyanide ion in water.…”
mentioning
confidence: 99%
“…Many metal complexes are known in the literature for the detection of cyanide using colorimetric and fluorescent approaches. However, most of these reported complexes needed expensive reactants, multistep synthesis of ligand, purification by different separation techniques, and different characterization techniques were required, and they are very time-consuming. To avoid the multistep synthesis and characterization, we have found that an off-the-shelf compound, 6,7-dihydroxycoumarin ( 1 ), is suitable to make a complex with copper in water and thereby binds with cyanide ion in water.…”
mentioning
confidence: 99%
“…The mechanisms of fluorescent sensing CN – with coumarin derivatives are mainly based on the nucleophilic addition on the coumarin or the displacement of coumarin from coumarin-copper complexes . Among the chemosensors based on nucleophilic addition mechanism, CN – reactive sites include the 4-position of the coumarin group, and polarized C  C , ,, C  N , and C – N , bonds conjugated to coumarin.…”
Section: Fluorescent Chemosensors Based On Coumarin Platform For Anionsmentioning
confidence: 99%
“…The equation LOD=3σ/ K was utilized to deduce the limit of detection (LOD) (Figure S13) [21] . The calculated LOD value was 1.48×10 −7 M (26.24 ppb).…”
Section: Resultsmentioning
confidence: 99%